Programmed death-ligand 1 expression and tumor-infiltrating lymphocytes in non-small cell lung cancer: association with clinicopathologic parameters - Gaurav Garg; Kuruswamy Thurai Prasad; Navneet Singh; Parul Gupta; Valliappan Muthu; Ashim Das; Amanjit Bal (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Background Data on the prevalence of programmed death-ligand 1 (PD-L1) expression and tumor-infiltrating lymphocytes (TILs) in non-small cell lung cancer (NSCLC) and their clinical significance in Indian patients are limited. Methods Newly diagnosed NSCLC cases (adenocarcinoma or squamous cell carcinoma [SqCC] histology) were included in the present study. The TILs were evaluated based on morphology on hematoxylin and eosin-stained slides. PD-L1 expression in tumors was assessed using immunohistochemistry with rabbit monoclonal antibody (SP263) on the Ventana automated immunostainer. Tumors with PD-L1 expression > 50% on tumor cells were considered PD-L1-positive. Tumors in which TILs occupy > 25% of stroma were considered to have high TILs. The association of PD-L1 expression and TILs with various clinical parameters including overall survival (OS) was investigated. Results The present study included 128 cases of NSCLC (67 adenocarcinoma, 61 SqCC). PD-L1 positivity was observed in 17.2% of the patients with NSCLC. Baseline characteristics of PD-L1-positive subjects were similar to PD-L1-negative subjects except for a higher prevalence of liver metastasis (18.2% vs. 2.8%; p = .018) and a higher probability of diagnosis from extrapulmonary biopsies. High TILs were observed in 26.6% of the subjects. However, PD-L1 expression and high TIL did not affect OS. Conclusions PD-L1 positivity and high TILs were observed in 20% and 25% of the patients with NSCLC, respectively, however, neither were predictors of survival in SqCC.